Regional Economic Development: The Industrial Agglomeration Area Development in Improving Economic Growth in Cilacap Regency - Aprianto, Naerul Edwin Kiky; Fauziah, Syarifa Nada; Oktaviani, Tia (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
The inequality of economic development in the Cilacap Regency is an important issue that requires serious attention. Uneven economic growth, income disparity, and dependence on certain sectors are some of the main problems that need to be addressed. As the southern industrial region of Central Java, Cilacap Regency has great potential to become a centre of economic growth through the development of industrial agglomeration areas. Industrial agglomeration refers to the concentration of companies in a particular location, so as to increase economic growth and employment in the region. This research uses a qualitative-descriptive method with data analysis techniques using the Miles and Huberman model which includes data reduction, data presentation, and data verification/conclusion drawing. This research concludes that the Cilacap Industrial Estate, the Central Java Provincial Industrial Allotment Area, and the industrial allotment area consisting of the Bunton, Karangkandri, Warungbatok, and Tinggarjaya Industrial Allotment Areas are currently the concentration of industrial areas that are used as industrial agglomeration development areas in supporting economic development in Cilacap Regency. In its development, the government will also build Cilacap Industrial Park to support the KPI of Central Java Province located in Mertasinga Village (North Cilacap District) and Menganti Village (Kesugihan District). In addition, industrial agglomeration has a positive impact on economic growth in Cilacap Regency, especially through increased industrial efficiency and productivity.